Hexagonal boron nitride as a tablet lubricant and a comparison with conventional lubricants - UĞURLU, TİMUÇİN (ELSEVIER SCIENCE BV, 2008)
The objective of this study was to investigate the lubrication properties of hexagonal boron nitride (HBN) as a new tablet lubricant and compare it with conventional lubricants such as magnesium stearate (MGST), stearic acid (STAC), and glyceryl behenate (COMP). Tablets were manufactured on an instrumented single-station tablet press to monitor lower punch ejection force (LPEF) containing varied lubricants in different ratio (0.5, 1, 2%). Tablet crushing strength, disintegration time and thickness were measured. Tensile strength of compacted tablets were measured by applying a diametrical load across the edge of tablets to determine mechanical strength. The deformation mechanism of tablets was studied during compression from the Heckel plots with or without lubricants. MGST was found to be the most effective lubricant based on LPEF-lubrication concentration profile and LPEF of HBN was found very close to that of MGST. HBN was better than both STAC and COMP. A good lubrication was obtained at 0.5% for MGST and HBN (189 and 195N, respectively). Where COMP and STAC showed 20 and 35% more LPEF compare to that of MGST (239 and 288N, respectively). Even at the concentration of 2% COMP and STAC did not decrease LPEF as much as 0.5% of MGST and HBN. Like all conventional lubricants the higher the concentration of HBN the lower the mechanical properties of tablets because of its hydrophobic character. However, this deterioration was not as pronounced as MGST. HBN had no significant effect on tablet properties. Based on the Heckel plots, it was observed that after the addition of 1% lubricant granules showed less plastic deformation. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: lubricants; hexagonal boron nitride; tablets; lower punch ejection force (LPEF); magnesium stearate; MAGNESIUM STEARATE; POWDER COMPACTION; COMPRESSION